(untitled) (KULT_online, 2011)
The metropolis as a source of modern arts—this is the subject of an anthology published in 2010 by Gebr. Mann Verlag. The volume is based on an interdisciplinary series of lectures which have been held at the school of arts of Ludwig Maximilians University Munich. In 17 articles, city planning, painting, design, photography, music, theatre, preservation of monuments, and film are depicted as metropolis-related arts. It varies how convincingly the contributions display the interdisciplinarity at which the book aims.